Still Using the Wrong Yardstick: Measuring Quality by the Proxies of Bias, Conformity, and Rumor - Dyson, Maurice R. (Columbia Journal of Gender and Law, 2015)
It is well overdue to confront the three main ill-advised measurements that perpetuate persistent discrimination in legal academia: bias, conformity, and rumor. When proxies for quality are measured by benchmarks of innuendo, it does a disservice to the legal academy, the individual faculty, the student body, and the legal profession that is shaped by that culture and set of practices. Furthermore, what is valued as noteworthy contributions to service, teaching, and scholarship remains a rigged and biased system of evaluation that is detrimental to the educational process. Finally, conformity to the majority may also operate as a disservice by marginalizing divergent voices in a way that is harmful to academic freedom and the intellectual robustness of the academy. When non-conformity is admirable in raising student awareness or introducing alternative effective models of pedagogy or perspective, it should be rewarded rather than penalized. Yet penalization is too often precisely what happens, and many in legal academia are caught in a perfect storm trifecta of bias, rumor, and the sanctions imposed for non-conformity. The machinery of maligning rumor, once initiated, is difficult to cease or reverse course. How much of one’s reputation lies in the hands of close friends in a close-knit, so-called “old buddy” network, in the criticism of avowed colleagues or students with an axe to grind, or in institutional affiliation is quite disturbing, and even more so when it indelibly shapes decisions of appointment, tenure, promotion, retention, recognition, and pedagogy. Rumor is processed as truth—spread, repeated, perpetuated, and never questioned.